Reboot/NoFap Participants Erectile Concerns Predicted by Anxiety and Not Mediated/Moderated by Pornography Viewing. Issue 4 (October 2022) - Prause, Nicole; Binnie, James
"Reboot" coaches claiming to treat pornography addiction increasingly claim to treat erectile dysfunction (ED). They view ED as due to pornography viewing. However, anxiety has long been the best predictor of ED. We hypothesized that those involved in Reboot treatments would report erectile difficulties predicted by anxiety symptoms and not pornography viewing. Six-hundred and sixty-nine participants familiar with Reboot treatments completed a series of online questionnaires. Among those who participated in Reboot treatments, anxiety symptoms predicted ED. Pornography viewing frequency did not mediate or moderate this relationship. Licensed providers should work to dispel this apparent health disinformation by life "Reboot" coaches.